Cost-effectiveness of occupational therapy for older adults: a protocol for an updated systematic review - Takao Kaneko; Hirofumi Nagayama; Kohei Ikeda; Takuto Nakamura; Ayaka Niimi; Natsuki Inoue; Taisei Takeda; Junya Uchida (BMJ Open)
Introduction The ageing populations in developed countries are a global concern, with increasing numbers of older adults facing physical, cognitive and psychological challenges, resulting in reduced quality of life and higher healthcare costs. Healthcare expenditure worldwide has been on the rise, especially among older adults, emphasising the importance of enabling independent living while reducing healthcare costs. Occupational therapy holds promising outcomes in promoting functional independence and enhancing the quality of life for older adults, but research on its cost-effectiveness remains limited. This systematic review aims to evaluate the recent evidence on the cost-effectiveness of occupational therapy interventions for older adults from a pragmatic perspective.Methods and analysis This systematic review will cover full economic evaluations, including cost-effectiveness, cost-utility and cost–benefit analyses, by reviewing randomised and cluster randomised controlled trials. The participants will be aged over 65 years without disease or disability restrictions. Primary outcomes will be assessed using functional status and quality-of-life assessments. Studies published before July 2023 will be searched in PubMed, Web of Science and Cumulative Index to Nursing and Allied Health Literature (CINAHL) databases, with no language restrictions.Ethics and dissemination Ethical approval is not required for this literature-based systematic review. The study’s findings will update the evaluation of occupational therapy’s cost-effectiveness in older adults and will be made public by publishing them in scholarly journals.PROSPERO registration number CRD42023453558.